Нанесение тонких пленок в вакууме на подложки из синтетического опала - Panfilov, Yu. V.; Samoylovich, M. I.; Bulygina, E. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The influence of thermal evaporation, ion-plasma magnetron sputtering, and ion-beam deposition methods of thin films on the surface characteristics of photonic crystals is examined. Schemes of thin film formation processes on opal matrices and designs of technological equipment are presented. The results of electrical resistance measurements of the films and surface topography characteristics of photonic crystal samples obtained using an atomic force microscope are provided.